Collaborative climate mitigation and adaptation planning with university, community, and municipal partners: a case study in Anchorage, Alaska. Issue 9 (1st September 2020) - Hahn, Micah B.; Kemp, Catherine; Ward-Waller, Chelsea; Donovan, Shannon; Schmidt, Jennifer I.; Bauer, Stephanie
ABSTRACT: Cities around the world are creating formal planning documents proposing local actions to mitigate and prepare for the impacts of climate change. Despite a growing number of examples of such plans and "toolkits" that outline the process for undertaking these planning efforts, many cities are still struggling to know where to start. Furthermore, meta-analyses of existing climate action plans show that many suffer from similar limitations including lack of scientific input, failure to consider strategies across multiple sectors within local government, limited public involvement, narrow focus on mitigation, and lack of detail regarding implementation and monitoring. This paper describes our process for developing the Anchorage Climate Action Plan and our experience fusing a three-way partnership between the municipal government, a local university, and the broader Anchorage, Alaska community. We describe the nuts and bolts of our funding, leadership structure, and technical working sessions and reflect on the key structural, political, and social elements that catalysed plan development, adoption, and implementation. Our experience suggests that public support from municipal leaders, commitment from local experts, a dedicated steering committee, a diverse set of stakeholders, and a good working relationship with the local government officials (e.g. Assembly members or City Council) are critical to creating a successful framework for climate mitigation and adaptation planning in a community. Collaborative planning with a local university that prioritises community-engagement can support the development of a robust planning document that integrates local scientific expertise and is representative of the community it is meant to serve.